KINETIKA ADSORPSI AMMONIUM DARI KOPOLIMER SELULOSA JERAMI PADI DENGAN ASAM AKRILAT DAN AKRILAMIDA - Wina Yulianti (Jurnal Biofisika, 2012)
Copolymerization  of  cellulose  from  rice  straw  with  acrylic  acid  and  acrylamide produce  biodegradable  superabsorbent  Copolymerization  was  carried out  at  65  C under nitrogen athmosphere.  Initiator and cross linking agent  used were potassium peroxodisulfate  and  N'N-methylene  bis  acrylamide.  Superabsorbent  produced  is anionic,  that  can  bind  ammonium  cation.  The  kinetics  of  swelling  adsorption  was following pseudo second-order equation.